The role of physicochemical and topological parameters in drug design - Darlami, Janki; Sharma, Shweta (Frontiers in Drug Discovery, 2024)
Quantitative structure activity relationship (QSAR) is a widely used tool in rational drug design which establish relations between the physicochemical and topological descriptors of ligands with their biological activities. Obtained QSAR models help to identify descriptors which play pivotal role in the biological activity of ligands. This not only help to predict new compounds with desirable biological activity but also helps to design new compounds with better activities and low toxicities. QSAR commonly uses Lipophilicity (LogP), Hydrophobicity (LogD), Water solubility (LogS), Acid-Base dissociation constant (pKa), Dipole Moment, Highest occupied molecular orbital (HOMO), Lowest unoccupied molecular orbital (LUMO), Molecular weight (MW), Molar volume (MV), Molar refractivity (MR) and Kappa index as physicochemical parameters. Some commonly used topological indices in QSAR are; Wiener index, Platt indices, Hosoya index, Zagreb indices, Balaban index and Estate index. This review presents brief description of significance of most extensively used physicochemical and topological parameters in drug design.